Securing the corporate sustainability advantage - Joshi, Havovi (Institutional Knowledge at Singapore Management University, 2019)
The UN Global Compact is the largest sustainable business initiative in the world, with more than 70 local chapters that work with close to 10,000 companies, large and small, across the world. With 3,000 stakeholders, we are a true multi-stakeholder initiative. We were founded 19 years back by former UN Secretary-General, Kofi Annan, with a view to giving the organisation a human face. So Mr. Annan put forward Ten Principles relating to UN conventions—spanning human rights, labour, environment and anti-corruption. These principles constitute the foundation of what we think of as corporate sustainability, and all companies that join the UN Global Compact must sign up to these principles and report on them once a year. We then make this reporting available to everyone.